Lowering Saudi Arabia's fuel consumption and energy system costs without increasing end consumer prices - Matar, Walid; Murphy, Frederic; Pierru, Axel; Rioux, Bertrand (Energy economics, 2015)
Using a multi-sector equilibrium model of the Saudi energy system that handles administered prices in a mixed-complementarity formulation, we present results from a set of policy scenarios that lower oil consumption in the country. Some of these scenarios are the solutions to Mathematical Programs subject to Equilibrium Constraints (MPECs) that maximize the net economic gain for the Saudi economy. The policies examined have the potential to generate economic gains exceeding 23 billion USD in 2011, or about 4% of Saudi Arabia's GDP. This economic gain comes mainly from inter-sectoral fuel pricing policies that incent shifting the mix in technologies that generate electricity and produce water from energy intensive technologies to more efficient ones. We show that when complemented by credits for investments in solar and nuclear power generation capacities, a modest increase in the transfer prices of fuels among sectors is sufficient to produce economic gains close to those achieved by deregulating transfer prices. The approach we develop here is an alternative to the classic recommendation of deregulating inter-sectoral fuel prices in situations where the conditions for successful liberalized markets do not exist. It is a template for introducing the notions of incentivizing behavior using prices into countries that rely more on administrative procedures than markets, leading to a deeper understanding of how markets can lead to economic gain. •The policies examined would have potentially generated economic gains exceeding 23 billion USD in 2011.•We design policies that produce economic benefits close to those achieved by deregulating inter-sectoral fuel prices.•This paper provides a template for building multi-sector models when transfer prices between sectors are administered.